ANALISYS AND MAPPING OF ENVIRONMENTAL SENSITIVITY INDEX IN BANGGAI REGENCY AND BANGGAI ISLANDS REGENCY, CENTRAL SULAWESI - Sugeng Putranto; Neviaty P. Zamani; Harpasis S. Sanusi; Etty Riani; Achmad Fahrudin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The Environmental Sensitivity Index (ESI) is a description of the biological, socio-economic and socio-cultural values of a particular coastal and marine area used as a priority response to oil spills, shown on a map by applying spatial analysis using geographic information system technology. The purpose of this research was to analyse mangrove ecosystem area in Banggai and Banggai Islands Regency based on its vulnerability value by analyzing mangrove community structure and socio-economic services for local community. The research was conducted in nine sub-districts, among others: South Batui, Batui, East Luwuk, Lamala, Masama, Balantak, Bualemo (Banggai) and Bulagi and Buko (Banggai Islands). The study was conducted from August to November 2016, with field observations, direct interviews with communities and local government and literature review. The results of spatial analysis of ESI in the coastal areas of Banggai and Banggai Islands are obtained from sensitivity values of medium and sensitive. Areas with moderate sensitivity are Batui, East Luwuk, Masama, Lamala, Balantak and Bualemo sub-districts with grades of 16,78 – 24,35. The value of ESI with sensitive category ranges from 38,24 – 57,54 in Bulagi, Buko and South Batui sub-districts. Keywords: mangrove ecosystem, Environmental Sensitivity Index (ESI)